Proceedings of the 12th International Conference on Kinanthropology Sport and Quality of Life. 7. - 9. 11. 2019 - Ban, Maja (Masaryk University Press, 2020)
Proceedings of the 12th Conference of Sport and Quality of Life 2019 gatheres submissions of participants of the conference. Every submission is the result of positive evaluation by reviewers from the corresponding field. Conference is divided into sections - Analysis of human movement; Sport training, nutrition and regeneration; Sport and social sciences; Active ageing and sarcopenia; Strength and conditioning training; section for PhD students.